Participant observation for inquiry-based learning: a document analysis of exam papers from an internship-course for master’s students in health services research in Germany - Ullrich, Charlotte; Ziegler, Sandra; Armbruster, Alicia; Wensing, Michel; Klafke, Nadja (BMC medical education, 2024)
Inquiry-based learning (IBL) is a type of problem-based learning. While IBL aims at reflecting the work of practicing researchers, only some students will pursue an academic career. We therefore designed a course that provides opportunities for IBL by applying participant observation to internship work experience inside and outside academia. Using this internship course as an example, we investigated, how master’s students in health science executed an IBL assignment regarding the application of participant observation and presentation of findings. In addition, the understanding of occupational fields provided through the IBL assignment was examined. To determine whether learning objectives were met, a document analysis of IBL assignments comprising presentation slides and field protocols was performed. Within content analysis, a category grid was used examining (a) suitability of chosen research objectives , (b) execution of field protocols , (c) sufficiency of reporting and (d) extent of reflection . 49 IBL assignments from the years 2020–2022 were included. Sides of IBL observations were: (a) organizations providing health care ( n = 28); (b) administrations of health care ( n = 8); and (c) research institutes ( n = 13). Within students’ field protocols, the level of detail of descriptions differed. 30 assignments included reflection on the methods used and research experience. In about a third of IBL assignments, indication of observation type, theoretical background and data analysis was missing. Using participant observation of internship work-experience for IBL can serve as a teaching tool for students to develop methodological skills. For future courses, we developed a checklist to strengthen reporting, reflection and use of theory. As internships are often integrated in degree programs in health sciences similar courses could be implemented in different programs, given qualified methodological guidance.